Meningkatkan Keterampilan Berpikir Kritis dan Pemecahan Masalah melalui Model Creative Problem Solving dalam Pembelajaran Geografi di Madrasah Aliyah - Suryadi, Roni (MAN Insan Cendekia Siak, 2025)
This study aims to enhance students’ critical thinking and problem-solving skills in Geography through the implementation of the creative problem solving (CPS) model. The research was conducted in class XII IIS 1 at MAN Insan Cendekia Siak, with 21 students as the subjects. The method used was classroom action research, consisting of two cycles, each involving planning, action, observation, and reflection stages. Data were collected through observation sheets, critical thinking and problem-solving tests, and field notes. The results indicated a significant improvement in students’ critical thinking and problem-solving abilities. In cycle 1, critical thinking skills reached 71.4% (good category) and increased to 81.9% (very good) in cycle 2. Meanwhile, problem-solving skills improved from 52.38% (fair) in cycle 1 to 92.53% (very good) in cycle 2. Test results also showed similar improvements, with critical thinking increasing from 73.80% to 84.77% and problem-solving from 66.66% to 90.47%. Thus, the CPS model proved effective in enhancing students’ critical thinking and problem-solving skills in geography learning.